1946
DOI: 10.2307/1538033
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Texture and Composition of Surface on the Attachment of Sedentary Marine Organisms

Abstract: vas and the IToods Hole Oceanographic Institution * Marine installations of various kinds necessitate exposure of construction materials under sea water. Data dealing with the amount of fouling accumulated by such materials are not abundant. Information which might be of aid to the scientist seeking the most favorable material upon which to collect sedentary organisms for study is also scanty. The present study was undertaken to determine the effect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

1953
1953
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 1 publication
2
24
0
1
Order By: Relevance
“…This issue needs to be added to the long list of considerations for studies involving settlement panels, such as the size (Jackson 1977, Osman 1977, Keough 1984, Butler 1991 and surface characteristics of the panels (e.g. texture: Pomerat & Weiss 1946, Crisp & Ryland 1960, complexity: Bourget et al 1994, Walters & Wethey 1996, composition: Raimondi 1988, McGuinness 1989, Anderson & Underwood 1994.…”
Section: Discussionmentioning
confidence: 99%
“…This issue needs to be added to the long list of considerations for studies involving settlement panels, such as the size (Jackson 1977, Osman 1977, Keough 1984, Butler 1991 and surface characteristics of the panels (e.g. texture: Pomerat & Weiss 1946, Crisp & Ryland 1960, complexity: Bourget et al 1994, Walters & Wethey 1996, composition: Raimondi 1988, McGuinness 1989, Anderson & Underwood 1994.…”
Section: Discussionmentioning
confidence: 99%
“…Conflictingly, Raimondi (1988) found differences in the recruitment levels of Chthamalus anispoma barnacles on granite and basaltic rocks, attributing these differences to post-settlement mortality. Other authors, using a variety of natural and artificial substrata have all found differences in the settlement density of barnacles in situ on silanes, bakélite, glass, asbestos, Perspex, PVC, metals, ceramics, slate, Tufnol, wood and beeswax (Pomerat & Reiner, 1942;Pomerat & Weiss, 1946;Gregg, 1948;Pyefinch, 1948;Crisp & Barnes, 1954;Meadows, 1969 andWalker, 1987).…”
Section: Introductionmentioning
confidence: 96%
“…Such a surface affordsa better key for settlement (see Barnes, Crisp & Powell, 1951), and also is less easily desiccated (see Pomerat & Reiner, 1942;Pomerat & Weiss, 1946;Barnes & Crisp, 1953).…”
Section: Settlement and Survival On The Intertidal Panelsmentioning
confidence: 99%